Revealing the Impact of Underage Marriage: How is Household Welfare Adversely Affected? - Aliyah, Nelud Darajaatul; Atmari, Atmari; Darmawan, Didit; Rizky, Muchammad Catur; Farid, Mohamad (Bulletin of Science, Technology and Society, 2023)
Family life through marriage is one of the pages of life that every human being will go through. That's when the maturity of the married couple is very much demanded in order to achieve success in building a household ark. Underage marriage is a marriage between a man and a woman whose age has not reached the age limit for marriage, where the age limit for marriage is regulated by law. According to Law Number 16 of 2019, Article 7 paragraph (1), marriage is only permitted if the man and woman have reached the age of 19 (nineteen) years. It is hoped that this age restriction on marriage will make couples more prepared to undergo household marriage. The location of this research was carried out in a village in Sidoarjo district. The purpose of this paper is to provide education about the relationship between underage marriage and household welfare and explain what kind of influence it will have. This research uses a quantitative approach. Primary data was obtained directly from respondents, namely from married couples who married underage in one of the villages in Sidoarjo district. The sample in this study amounted to 30 people who entered into underage marriages, where all the population was used as respondents. The results of this study confirm that there is indeed an influence of underage marriage on household welfare.